High performance alkyd resins synthesized from postconsumer PET bottles. Issue 76 (19th August 2015) - Spasojević, P. M.; Panić, V. V.; Džunuzović, J. V.; Marinković, A. D.; Woortman, A. J. J.; Loos, K.; Popović, I. G.
<x xml:space="preserve">Abstract</x> A new perspective for mass production of alkyd resins from multifunctional glycolyzates obtained from waste PET – a step up to greener production and excellent applicative properties.